Financial Management Strategies and Their Impact on the Profitability of Traditional Clothing Rental MSMEs in Malang City - Margareta Fatmawati; Cakti Indra Gunawan; Warter Agustim; Fitria Setyaningrum (IRDH International Journal of Social Sciences & Humanities, 2026)
There are still various problems faced by Micro, Small, and Medium Enterprises (MSMEs), particularly in the aspect of financial management that has not been implemented optimally and in a structured manner. Inadequate financial management can directly affect business profitability, especially in traditional clothing rental service MSMEs that have unstable income characteristics and are influenced by seasonal factors. This study aims to identify the financial management strategies applied and to analyze internal and external factors in an effort to increase the profitability of the Ibu Diyah Traditional Clothing Rental MSME in Malang City. This research employs a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation using primary and secondary data sources. The data analysis method used is SWOT analysis, including the preparation of IFAS and EFAS matrices, the determination of SO, ST, WO, and WT strategies, and the mapping of the business position in the IE matrix. The results indicate that financial management at the Ibu Diyah Traditional Clothing Rental MSME remains simple and unstructured, as reflected in manual financial recording, the absence of periodic financial statements, and the lack of systematic financial planning and control. Based on the SWOT analysis results, strength and opportunity factors are more dominant than weakness and threat factors, indicating that the business is in a fairly good condition and has the potential to grow.